Analisis Rasio Likuiditas dan Profitabilitas untuk Menilai Kinerja Keuangan pada PT TASPEN (Persero) - Miki Indika; Anggia Syafitri (Jurnal Kajian Akuntansi dan Auditing, 2019)
The purpose of this study is to assess the financial performance of PT TASPEN (Persero) assessed from the Analysis of Liquidity Ratios and Profitability Ratios. The data used in this study are quantitative data, namely financial statement data for the last three years from 2015 to 2017. Analysis of the data used is quantitative analysts by presenting tables, graphs or numbers, with the data analysis techniques used, namely data analysis techniques manually. The results of this study indicated that the company's financial performance was assessed from the level of liquidity in unfavorable conditions, this is because the current ratio, cash ratio, and debt turnover ratio were below the industry average, and when viewed from the profitability ratio the company was almost good , where the results of the calculation of the ratio of net profit margin, ROI, ROA, and earnings per share continued to increase even though the value of the ratio was still below the industry average.